2017
DOI: 10.1038/s41598-017-11638-7
|View full text |Cite
|
Sign up to set email alerts
|

Predicted effects of observed changes in the mRNA and microRNA transcriptome of lung neutrophils during S. pneumoniae pneumonia in mice

Abstract: The complex role of neutrophils in modulating the inflammatory response is increasingly appreciated. Our studies profiled the expression of mRNAs and microRNAs (miRs) in lung neutrophils in mice during S. pneumoniae pneumonia and performed in depth in silico analyses. Lung neutrophils were isolated 24 hours after intratracheal instillation of PBS or S. pneumoniae, and differentially expressed (DE) mRNAs and miRs were identified. Lung neutrophils from mice with S. pneumoniae pneumonia contained 4127 DE mRNAs, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 69 publications
1
15
0
Order By: Relevance
“…Mice given ALI induced by Streptococcus pneumoniae ( Sp ) were studied 6 days after infection, a time point during resolution when infected mice have regained much of their weight loss (Gomez et al, ; Matute‐Bello et al, ) Mice lacking IFN‐γ had a similar weight loss and return to baseline weight by 6 days post‐ Sp , compared to WT mice (Figure a). In prior reports, similar inocula of Sp did not demonstrate a difference in bacterial clearance between genotypes (Yamada et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice given ALI induced by Streptococcus pneumoniae ( Sp ) were studied 6 days after infection, a time point during resolution when infected mice have regained much of their weight loss (Gomez et al, ; Matute‐Bello et al, ) Mice lacking IFN‐γ had a similar weight loss and return to baseline weight by 6 days post‐ Sp , compared to WT mice (Figure a). In prior reports, similar inocula of Sp did not demonstrate a difference in bacterial clearance between genotypes (Yamada et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…By day 7 post‐injury, resolution is underway; type II epithelial cell (AT2) proliferation is high, lymphocyte numbers are increasing, and neutrophils and inflammatory macrophages are decreased. Two other stimuli that are important common causes of lung injury ( S. pneumoniae and H1N1 influenza) were also studied to identify and compare the effects of IFN‐γ deficiency at a time point during resolution when mice have regained much of their weight loss (Arpaia et al, ; Gomez et al, ; Matute‐Bello, Frevert, & Martin, ). These studies identified the contribution of IFN‐γ both to lung injury and to changes in immune cell kinetics during resolution from lung injury.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the expression of mmu-miR-21a-5p, mmu-miR-147-3p, mmu-miR-449a-5p, and mmu-miR-703 was deregulated in the lungs of mice exposed to multi-walled carbon nanotubes [24] and mmu-miR-342-3p in mice exposed to nano-TiO2 particles [25]. The deregulation of the miRNAs observed in our study was further found in the lungs of mice after cigarette smoke exposure (mmu-miR-21a-5p, mmu-miR-135b-5p, mmu-miR-146a-5p, mmu-miR-146b-5p, mmu-miR-155-5p, mmu-miR-342-3p, mmu-miR-449a-5p, mmu-miR-489-3p, and mmu-miR-672-5p) [26], in mice with cigarette smoke induced atherosclerosis (mmu-miR-21a-5p and mmu-miR-155-5p) [27], in the lungs of mice after radon inhalation (mmu-miR-21a-3p, mmu-miR-135b-5p, mmu-miR-146b-5p, mmu-miR-1298-5p, mmu-miR-6972-5p, and mmu-miR-703) [28], in mice with lung tumors (mmu-miR-135b-5p, mmu-miR-146b-5p, mmu-miR-223-3p, and mmu-miR-1298-5p) [29][30][31], in an ovalbumin-induced asthma mouse model (mmu-miR-21a-5p, mmu-miR-135b-5p, mmu-miR-146a-5p, mmu-miR-155-5p, mmu-miR-223-3p, and mmu-miR-451a) [32], and in mice with pneumonia and influenza infections (mmu-miR-21a-5p, mmu-miR-144-5p, mmu-miR-155-5p, and mmu-miR-223-3p) [33][34][35]. This overall suggests that the inhalation of CuO NPs induces a similar response as the above-mentioned adverse conditions and therefore likely has negative effects on the organism.…”
Section: Discussionmentioning
confidence: 99%
“…Following BAL collection, a single cell digest was generated from the right lung of each mouse using enzymatic digestion and mechanical disruption, as previously described [3941]. After lysis to remove red blood cells, the single cell digest was stained to identify neutrophils using CD45 and Ly6G.…”
Section: Methodsmentioning
confidence: 99%